Challenges of service learning practices: student and faculty perspectives from Malaysia - Yusof, Norhafezah; Tengku Ariffin, Tengku Faekah; Awang Hashim, Rosna; Nordin, Hasniza; Kaur, Amrita (Universiti Utara Malaysia Press, 2020)
Purpose – The primary aim of service learning is to produce holistically developed students. Despite the mandate from the Ministry of Higher Education, Malaysia to infuse service learning in the programs of studies since 2015, service learning in the country remains in its infancy. Critical insights concerning contextual compatibility are still missing in the Malaysian context. In this regard, the current paper aims to investigate the perspectives of lecturers and students on the challenges they have encountered while participating in service learning. Methodology – The study employed a qualitative approach and the principles of Scholarship of Teaching and Learning (SoTL) guided the collection of data. Students and lecturers who participated in the study were selected using purposive sampling techniques. The data from the students was collected using focus group interviews, while in-depth face to face interviews were used to collect data from the lecturers. These two sources of data were then analysed using a thematic analysis method.Findings – From the perspectives of the students, the challenges encountered were as follows: 1) there is a gap between theory and practice and 2) the lack of cognitive autonomy, while from the perspectives of the lecturers, the challenge was lack of structural support. There was also a theme seen in the common challenges experienced by the participants which was about the relationship and rapport with the community. Significance –The findings provide insights into the challenges faced by lecturers and students in a public university where service learning is practised. These insights may have implications for academic developers providing training workshops on service learning and for lecturers involved in the design and implementation of service-learning projects